Platelet-rich plasma for the treatment of discogenic low back pain: a prospective randomized controlled trial - Wang, Xiangyi; Wang, Siqi; Zhang, Jie; Xie, Gang; Zhang, Jin (Frontiers in Pain Research, 2025)
ObjectiveThis study aimed to compare the therapeutic effect of PRP and methylene blue injection in patients with discogenic low back pain.MethodsA total of 40 patients with discogenic low back pain were randomly divided into two groups, with 20 patients in group A receiving platelet-rich plasma injections and 20 patients in group B receiving methylene blue injections. Visual analog scale (VAS) scores, Japanese Orthopaedic Association (JOA) scores, Pfirrmann grades, and MRI apparent diffusion coefficients (ADCs) were recorded in both groups before the injections and 6 months after the injections.ResultsCompared with group B, the postoperative VAS score of group A was significantly decreased, while the JOA score and ADC score were significantly increased (P < 0.05). There was no significant difference in Pfirrmann grade between the two groups after surgery (P > 0.05). In group A, the Pfirrmann grade after surgery was lower than before surgery (P < 0.05), and the ADC score was higher than before surgery (P < 0.05). There was no significant difference in Pfirrmann grade for the patients in group B before and after surgery (P > 0.05), and their ADC score was lower than that before surgery (P < 0.05).ConclusionCompared with a methylene blue injection, platelet-rich plasma can significantly reduce pain, improve the function of the lumbar spine, increase the diffusion ability of water molecules in the intervertebral disc, and improve the degree of intervertebral discogenic degeneration in patients with discogenic low back pain.